Current evaluation and management of plastic bronchitis in the pediatric population. (March 2020) - Li, Youjin; Williams, Ryan J.; Dombrowski, Natasha D.; Watters, Karen; Daly, Kevin P.; Irace, Alexandria L.; Visner, Gary A.; Rahbar, Reza; Fynn-Thompson, Francis
Abstract: Objective: To describe a multidisciplinary approach for the treatment of plastic bronchitis (PB) in children. Methods: Retrospective chart review of children with PB between 1997 and 2017. Data regarding clinical presentation, diagnosis, management, and outcomes were analyzed. Results: Of 34 patients presenting with PB, 24 had single ventricle (SV) heart disease, 9 had pulmonary disease, and one had no underlying disease. Median (IQR: interquartile range) age at the time of PB diagnosis was 5.5 years (IQR: 9.0). Presenting symptoms included cough productive of casts (n = 27, 79%), wheezing (n = 5, 15%), dyspnea (n = 18, 53%), hypoxia (n = 31, 91%), and respiratory failure (n = 9, 26%). Diagnosis was made based on clinical evaluation, bronchoscopy findings, and/or pathology of casts. Treatment methods included bronchoscopy for cast removal (25% of SV patients, 91% of non-SV patients), chest physiotherapy (SV: 92%, non-SV: 45%), albuterol (SV: 79%, non-SV: 73%), inhaled steroids (SV: 75%, non-SV: 18%), nebulized hypertonic saline (SV: 29%, non-SV: 9%), nebulized heparin (SV: 8%, non-SV: 55%), nebulized tissue plasminogen activator (tPA; SV: 33%, non-SV: 9%), inhaled Dornase Alfa (SV: 54%, non-SV: 9%), antibiotics (SV: 46%, non-SV: 45%), systemic steroids (SV: 13%, non-SV: 45%), and lymphatic embolization (SV: 8%, non-SV: 45%). Of SV patients, 11 had no recurrence, 5 underwent heart transplantation, one awaits transplant, and 3 died due to cardiac disease. Three patients with respiratory disease had recurrent PB and one died from MRSA pneumonia. Conclusion: PB is a highly morbid disease with limited treatment options. Bronchoscopy and chest physiotherapy for airway clearance are among the most-utilized therapies.